Determinants of Student Behavior to Use Financial Technology (Fintech) Banking Services - Integrated Theory of System Acceptance and Psychological Behavioral Theory - Fachrurrozie Fachrurrozie; Indah Anisykurlillah; Hasan Mukhibad; Kuat Waluyo Jati; Ahmad Nurkhin (Bright Publisher, 2026)
Fintech provides technology-based banking and financial services; therefore, the analysis of FinTech usage behavior should be viewed in the context of system acceptance and psychological behavioral theory. We employ the System Acceptance Theory approach, specifically the Theory of Acceptance Model, and the psychological behavioral theory, the Theory of Reasoned Action, to explain behavioral intention to use FinTech and incorporate risk factors. This study aims to prove the influence of perceived ease of use, perceived usefulness, subjective norms, attitude, and perceived risk on the intensity of Generation Z's intention to use Fintech. Moreover, this research demonstrates the influence of intention to use Fintech on fintech usage behavior. This research employed a survey approach with 350 students in Indonesia, who are part of Generation Z, and analyzed the data using Structural Equation Modeling with Partial Least Squares. We report that perceived ease of use and perceived usefulness are vital factors in increasing the intention to use Fintech. Attitude is a factor that encourages students to use Fintech, and conversely, perceived risk is a vital factor in decreasing intention to use Fintech. We were unable to find evidence of a relationship between subjective norms and intention to use Fintech. Ultimately, behavioral intention in using Fintech is crucial for increasing student adoption of Fintech. This study recommends that financial institutions offer Fintech services to enhance usability, convenience, and mitigate the risks associated with fintech use.